Electrochemical functionalization of Au by aminobenzene and 2-aminotoluene. (12th February 2016) - Rösicke, F; Sun, G; Neubert, T; Janietz, S; Hinrichs, K; Rappich, J
Abstract: Au surfaces are functionalized by aminobenzene (AB) and 2-aminotoluene (AT) using the electrochemical reduction of diazotized 1, 4-diaminobenzene and 2, 5-diaminotoluene. The IR spectroscopic measurements reveal the successful modification of Au surfaces by AB and AT. Both types of layers show similar thicknesses as obtained by microgravimetric measurements via electrochemical quartz crystal microbalance (EQCM). However, the faradaic efficiency for the grafting of AT onto an EQCM-Au sensor was 6% compared to 41% for the grafting of AB. This behavior points to a steric hindrance during the binding of AT to the EQCM surface induced by the additional methyl group present in the toluene derivative. The AB and AT functionalized surfaces have been further modified by the amidation reaction of EDC/NHS activated 4-nitrobenzoic acid. This model system reveals that the amidation reaction is slightly hindered in case of the AT layer due to the presence of the methyl group close to the amino group. This behavior leads to a four times less amount of amide bonds at the AT compared to AB modified Au surfaces as obtained from IR spectroscopic measurements.